Examination of Vehicles Carrying Fast-Breaking Cargo - Zokirov Dostonbek; Mamasoliyev Bunyodbek (Genius Journals, 2022)
The expert concludes on the general condition of the vehicle. In the event of a positive conclusion regarding the general condition of the body, it is recommended to evaluate the vehicle for a period of three years according to the category originally established by the plant that produced it, and the vehicle is sent for carrying out the determination of its isothermal characteristics
Keywords: Manometers; SPS; car; vehicle